Effect of Pulse Shaping on Subharmonic Aided Pressure Estimation In Vitro and In Vivo. (10th December 2016) - Gupta, Ipshita; Eisenbrey, John; Stanczak, Maria; Sridharan, Anush; Dave, Jaydev K.; Liu, Ji‐Bin; Hazard, Christopher; Wang, Xinghua; Wang, Ping; Li, Huiwen; Wallace, Kirk; Forsberg, Flemming
Abstract : Objectives: Subharmonic imaging (SHI) is a technique that uses the nonlinear oscillations of microbubbles when exposed to ultrasound at high pressures transmitting at the fundamental frequency ie, fo and receiving at half the transmit frequency (ie, fo /2). Subharmonic aided pressure estimation (SHAPE) is based on the inverse relationship between the subharmonic amplitude of the microbubbles and the ambient pressure change. Methods: Eight waveforms with different envelopes were optimized with respect to acoustic power at which the SHAPE study is most sensitive. The study was run with four input transmit cycles, first in vitro and then in vivo in three canines to select the waveform that achieved the best sensitivity for detecting changes in portal pressures using SHAPE. A Logiq 9 scanner with a 4C curvi‐linear array was used to acquire 2.5 MHz radio‐frequency data. Scanning was performed in dual imaging mode with B‐mode imaging at 4 MHz and a SHI contrast mode transmitting at 2.5 MHz and receiving at 1.25 MHz. Sonazoid, which is a lipid stabilized gas filled bubble of perfluorobutane, was used as the contrast agent in this study. Results: A linear decrease in subharmonic amplitude with increased pressure was observed for all waveforms ( r from −0.77 to −0.93; P  < .001) in vitro. There was a significantly higher correlation of the SHAPE gradient with changing pressures for the broadband pulses as compared to the narrowband pulses in both in vitro and in vivo results. The highest correlation was achieved with a Gaussian windowed binomial filtered square wave with an r ‐value of −0.95. One of the three canines was eliminated for technical reasons, while the other two produced very similar results to those obtained in vitro ( r from −0.72 to −0.98; P <.01). The most consistent in vivo results were achieved with the Gaussian windowed binomial filtered square wave ( r  = −0.95 and −0.96). Conclusions: Using this waveform is an improvement to the existing SHAPE technique (where a square wave was used) and should make SHAPE more sensitive for noninvasively determining portal hypertension.